2022
DOI: 10.3390/cells11213493
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Liquid Biopsy in Colorectal Cancer Screening: Current Challenges and Future Perspectives

Abstract: Colorectal cancer (CRC) represents the third most prevalent cancer worldwide and a leading cause of mortality among the population of western countries. However, CRC is frequently a preventable malignancy due to various screening tests being available. While failing to obtain real-time data, current screening methods (either endoscopic or stool-based tests) also require disagreeable preparation protocols and tissue sampling through invasive procedures, rendering adherence to CRC screening programs suboptimal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…SncRNAs encompass several subtypes, including microRNAs (miRNAs), small nucleolar RNAs, small nuclear RNAs, piwi-interacting RNAs, and tRNA-derived small RNAs [ 127 ]. Among them, miRNAs are the most extensively studied factors in cancer research, and liquid biopsy identifies miRNAs actively secreted by CTCs and tumour cells themselves [ 128 , 129 ]. MiRNAs can influence genes, with thousands of miRNAs regulating approximately 60% of the genes.…”
Section: Biomarkers and Detection Methodsmentioning
confidence: 99%
“…SncRNAs encompass several subtypes, including microRNAs (miRNAs), small nucleolar RNAs, small nuclear RNAs, piwi-interacting RNAs, and tRNA-derived small RNAs [ 127 ]. Among them, miRNAs are the most extensively studied factors in cancer research, and liquid biopsy identifies miRNAs actively secreted by CTCs and tumour cells themselves [ 128 , 129 ]. MiRNAs can influence genes, with thousands of miRNAs regulating approximately 60% of the genes.…”
Section: Biomarkers and Detection Methodsmentioning
confidence: 99%
“…The somatic mutations detectable in cfDNA could be instrumental in the rational assignment of immunotherapy and assessment of its effectiveness. For CRC, the total number of somatic mutations, also known as tumor mutation burden (TMB), could be one of the parameters to assess the response to immunotherapy [41,42] A high level of TMB (≥20 mutations/Mb) was found to be associated with microsatellite instability (MSI) or mutations in the two DNA polymerases (POLD and POLE) [42,43]. In a phase II trial, ctDNA was shown to be helpful in assessing the variant allele frequencies (VAFs) as a predictive biomarker for the immunotherapy of patients with solid tumors treated with an anti-PD1 agent.…”
Section: Ctdna For the Therapeutic Decisionmentioning
confidence: 99%
“…CRC is often diagnosed at an advanced stage, when the disease has already spread to the lymph nodes and/or more distant organs. Since survival in CRC patients improves with early diagnosis, there is an urgent need for screening programs that are able to identify specific and early disease markers [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%